2022
DOI: 10.1186/s12014-022-09389-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel plasma protein biomarkers from critically ill sepsis patients

Abstract: Background Despite the high morbidity and mortality associated with sepsis, the relationship between the plasma proteome and clinical outcome is poorly understood. In this study, we used targeted plasma proteomics to identify novel biomarkers of sepsis in critically ill patients. Methods Blood was obtained from 15 critically ill patients with suspected/confirmed sepsis (Sepsis-3.0 criteria) on intensive care unit (ICU) Day-1 and Day-3, as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Identification of accurate Long-COVID-specific biomarkers allows for early disease detection, accurate diagnosis, prognosis and/or targeted therapeutics. Advanced proteomic techniques, such as proximity extension assays [PEA; (Assarsson et al 2014 ; Lundberg et al 2011 ))] have great potential for an efficient and holistic approach to identifying disease and injury biomarkers (Fraser et al 2020a ; Fraser et al 2021 ; Iosef et al 2023 ; Van Nynatten et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of accurate Long-COVID-specific biomarkers allows for early disease detection, accurate diagnosis, prognosis and/or targeted therapeutics. Advanced proteomic techniques, such as proximity extension assays [PEA; (Assarsson et al 2014 ; Lundberg et al 2011 ))] have great potential for an efficient and holistic approach to identifying disease and injury biomarkers (Fraser et al 2020a ; Fraser et al 2021 ; Iosef et al 2023 ; Van Nynatten et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies based on sepsis‐3 diagnostic criteria also pointed out that MDW and WBC did not have an obvious predictive effect 16 . Cytokines such as IL10, CCL23, TGFα1, ST2, VSIG4, CNTN5 and ITGAV have also been mentioned in earlier research 17 . Due to the limited test conditions in this study, we did not examine other relevant data.…”
Section: Discussionmentioning
confidence: 69%
“… 16 Cytokines such as IL10, CCL23, TGFα1, ST2, VSIG4, CNTN5 and ITGAV have also been mentioned in earlier research. 17 Due to the limited test conditions in this study, we did not examine other relevant data. We anticipate that more sepsis markers will be identified in the future to facilitate the early diagnosis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…sST2 inhibits immune responses and results in myocardial injury by targeting ST2L/IL-33 interaction ( 14 ). Although sST2 is an inflammation biomarker in other conditions ( 16 , 17 , 30 , 31 ), its role in SIC is unclear. A previous study found sST2 elevation on days 1 and 3 of septic patients and correlated with lactate,which indicating illness severity ( 15 ).…”
Section: Discussionmentioning
confidence: 99%